Study on Efficiency of Voltage Sensor ZMPT101B and Current Sensor SCT-013 for Application in Power Distribution Monitoring System of 0.4KV Transformer - vorlachit, khamphon (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
In this research, performance testing was conducted on the ZMPT101B voltage sensor and the SCT-013 current sensor, which are single-phase AC electrical sensors, for application in a measurement and monitoring system for the energy output of 0.4 kV distribution transformers. For testing the voltage and current sensors, the electrical quantities were measured incrementally, and simultaneous measurements were taken using the standard measuring instruments of EDL. The results of both measurements were compared and analyzed to determine the accuracy and performance of the sensors. Subsequently, the findings were applied to develop a system for measuring and monitoring three-phase voltage and current of an actual distribution transformer. The system records and continuously reports data to an online central monitoring station 24 hours a day via a 4G mobile communication module, enabling real-time observation of phase voltages and currents for transformer monitoring purposes. Experimental results show that the average deviation of the voltage sensor across all three phases was 1.66 V compared with the standard measuring instrument, while the average deviation of the current sensor across all three phases was 0.036 A. For the implemented online measurement and monitoring system, installed on two real distribution transformers, successfully measured current and voltage values and transmitted the data to the central monitoring station. Analysis of the collected data allows determination of the periods of peak transformer current output as well as the current imbalance among the three phases.